Transition metals of arene derivatives with functionalized ionic liquid: DFT investigation, biological applications and electrochemical behavior of complexes - Rafikova, Khadichakhan; Meriç, Nermin; Güzel, Remziye; Arslan, Nevin; Binbay, Nil Ertekin; Kayan, Cezmi (ELSEVIER SCIENCE SA, 2022)
Mononuclear transition metal complexes based on ionic liquid have been prepared and characterized in detail. The biological properties of the three complexes were evaluated using radical scavenging activity, reducing power, antibacterial effect, DNA binding and cleavage activity. Among the complexes, [3-[(2R)-2-({[dichloro(η6 - benzene)ruthenium]diphenylphosphanyl}oxy)-2-phenylethyl]-1-methyl-1H-imidazol-3-ium chloride] (4), demonstrated the highest radical scavenging (64.7 %) and reducing power activity (0.467) at 200 μg/ml concentration. The highest zone of inhibition was obtained from [3-[(2R)-2-({[dichloro(η6 -p-cymene)ruthenium] diphenyl phosphanyl}oxy)-2-phenylethyl]-1-methyl-1H-imidazol-3-ium chloride] (3), against Bacillus cereus as 14 mm. Furthermore, all complexes were determined to have DNA binding and cleavage activities. Furthermore, theoretical DFT computations have also been carried out for the cationic complexes, to obtain minimum energy configuration of molecules. The effects of the chemical structures of three cationic complexes were also examined in relation to the variable property of electron-donating ligands for ruthenium-based complexes and iridium complex and their potential energy levels in ground and excited states HOMO and LUMO were determined.
Keywords: Ionic liquid; Biological assays; HOMO-LUMO; DFT calculation; Phosphinite Iridium; Ruthenium